History of the Concept of Restorative Justice in Resolving Child Criminal Cases (Study of Besilam Village, Langkat Regency) - Lidya Rahmadani Hasibuan; Syaiful Asmi Hasibuan; Nurbela Br. Purba (Yayasan Multidimensi Kreatif, 2024)
The development of the concept of restorative justice in the last 20 years has experienced very rapid development in several countries such as Australia, Canada, England and Wales, New Zealand and several other countries in Europe and the Pacific region. Likewise, in the United States, as a country that more often forms associations with countries to introduce repressive measures of punishment, America cannot avoid the strong influence of the development of restorative justice. Michael Tonry in 1999 began a survey of American sentencing policies with the results of his research obtaining several The living concepts regarding punishment until now, namely 1 structured sentencing, risk-based sentencing (sentence based on risk), indeterminate (sentence that does not determine) and restorative/community justice (recovery/community justice). So restorative justice is one of the punishment concepts that has been developed and is already running in the United States.